Association between Intrapancreatic Fat Deposition and Lower High-Density Lipoprotein Cholesterol in Individuals with Newly Diagnosed T2DM - Jianliang Wang; Qingyun Cai; Xiaojuan Wu; Jiaxuan Wang; Xiaona Chang; Xiaoyu Ding; Jia Liu; Guang Wang (International Journal of Endocrinology)
Background. Intrapancreatic fat deposition (IPFD) usually occurs in individuals with type 2 diabetes mellitus (T2DM), but its physiopathological influence remains controversial. The present study aimed to investigate IPFD and its associations with various aspects of glucose and lipid metabolism in individuals with newly diagnosed T2DM. Methods. A total of 100 individuals were included, consisting of 80 patients with newly diagnosed T2DM and 20 age- and sex-matched healthy controls. Then, we assessed IPFD using magnetic resonance imaging (MRI) and various parameters of glucose and lipid metabolism. Results. Individuals with newly diagnosed T2DM had a significantly higher IPFD (median: 12.34%; IQR, 9.19–16.60%) compared with healthy controls (median: 6.35%; IQR, 5.12–8.96%) p<0.001. In individuals with newly diagnosed T2DM, IPFD was significantly associated with FINS and HOMA-IR in unadjusted model (β = 0.239, p=0.022; β = 0.578, p=0.007, respectively) and adjusted model for age and sex (β = 0.241, p=0.022; β = 0.535, p=0.014, respectively), but these associations vanished after adjustment for age, sex, and BMI. The OR of lower HDL-C for the prevalence of high IPFD was 4.22 (95% CI, 1.41 to 12.69; p=0.010) after adjustment for age, sex, BMI, and HbA1c. Conclusions. Lower HDL-C was an independent predictor for a high degree of IPFD.